2016
DOI: 10.1515/ling-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

The prominence of spoken language elements in a sign language

Abstract: Code-blends in sign languages consist of simultaneously articulated manual signs and spoken language words. These "mouthings" (typically silent articulations) have been observed for many different sign languages. The present study aims to investigate the extent of such bimodal code-mixing in sign languages by investigating the frequency of mouthings produced by deaf users of Sign Language of the Netherlands (NGT), their co-occurrence with pointing signs, and whether any differences can be explained by sociolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…From the point of view of bilingual processing, our findings suggest there is more complex bilingual processing going on than simply the lexical co-activation of Dutch word forms with NGT signs, such as is likely taking place in the omnipresent use of redundant mouthings (see also Bank et al, 2016). The use of added mouthings, and especially the use of Dutch function words, suggests that Dutch morphosyntactic constructions or representations are activated in the production of NGT sentences.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…From the point of view of bilingual processing, our findings suggest there is more complex bilingual processing going on than simply the lexical co-activation of Dutch word forms with NGT signs, such as is likely taking place in the omnipresent use of redundant mouthings (see also Bank et al, 2016). The use of added mouthings, and especially the use of Dutch function words, suggests that Dutch morphosyntactic constructions or representations are activated in the production of NGT sentences.…”
Section: Discussionmentioning
confidence: 66%
“…We will use the same corpus as the studies above (Bank et al, 2011, 2015, 2016) and categorise the various occurrences of added mouthings and semantic mismatches. We will distinguish three varieties of special mouthings in this paper: Solo mouthings are isolated words or short phrases that occur while the hands are in rest position or otherwise engaged, and thus constitute code-switching rather than code-blending.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though widely recognized as a contact phenomenon, fingerspelling is not generally discussed within the context of code-mixing 1 (though code-blending has been attested in sign languages (Emmorey et al 2008, Bank et al 2016a, 2016b). Code-mixing, defined broadly, is the mixing of two or more languages (or dialects), within a sentence or a discourse.…”
Section: Fingerspelling As Code-mixingmentioning
confidence: 99%
“…Moreover, it should be noted that the data set was not very large, and this could possibly have influenced results. In a study of mouthings in Sign Language of the Netherlands (NGT), for instance, large differences between individuals were found, but no significant differences could be established when comparing groups of signers (Bank 2015, Bank et al 2015b. Another noteworthy finding is the spreading behavior: M found that almost half of the mouthings in the corpus spread leftward (mouthings anticipating the next sign), while rightward spreading (mouthings persevering over the next sign) is normally found more often in sign languages (e.g.…”
Section: Reviewed By Richard Bank Radboud University Nijmegenmentioning
confidence: 99%